“Intelligere”: reflections on individual connections, food and development (Research, Society and Development, 2022)
The present study deals with the “intelligere” (from the Latin, Inter = between, Legere = to choose) in food relationships and its importance in determining a possible future. This article will make a historical construction of food and its relationships in the development of societies, will correlate this construction with the forms and theories of development. It will deal with the bases of food production, especially family farming, with a transversal vision for Latin American specificities, establishing a relationship of vision and construction of centrality, interfaces, reflections, about eating and feeding a possible future. The reflections presented aim at proposing a course of construction of the very concept of food. It proposes that this construction has the “intelligere” as a central line and builds its theoretical line to understand why and how society is shifting and transforming “between choices”. It places the food theme at the center of development processes, referring to individuals, their relationships and personal, social, institutional constructions, the opportunity to configure the future scenarios of the life of ecosystems, with their substantive freedoms and collective responsibilities.